Tafsir Atas Teks Alkitab dalam Kaitannya dengan Toleransi Antarumat Beragama - Hendarto Supatra (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
Semansitcs is the study of meaning communicated through language. In the past time semantics was the study of meaning of words and sentences. Aboves sentence level which is known as text was never considered as linguistic semantics’ objek of study. Semantics which is a branch of structural linguistics only focused it’s attention on phones, morphemes, words, clauses, and sentences: substansive matters of language. Texts belong to speech or language system in use. The study of meaning in this area is called pragmatics or discourse analysis.Up to this time linguistics or semantics has been used as an instrument in interpreting the Holy Texts of many religions. In that period the Holy Texts interpretation activity was limited only on lexical and grammatical meaning. Today people are aware, that based on the theory of discourse analysis, texts should be considered as parts of discourse. To get the meaning of the texts significantly people must find the context, but this is the problems, that reconstructing the context of the text in its’origin is a never ending works. Since Holy Text interpretation is a kind of activity closed to mission of imposible, this should teaches us to be low hearted and tolerant to others